Kono-S anastomosis in Crohn's disease: initial experience in pediatric patients - Dotlacil, Vojtech; Lerchova, Tereza; Lengalova, Marketa; Kucerova, Barbora; Schwarz, Jan; Hradsky, Ondrej; Rygl, Michal; Skaba, Richard (Pediatric surgery international, 2024)
PURPOSE: Children diagnosed with Crohn's disease (CD) often undergo ileocecal resection (ICR) during childhood. Anastomotic recurrence is a frequent finding following this procedure. Data addressing the effect of the anastomosis type on disease recurrence are scarce in the pediatric population. The Kono-S anastomosis has shown promise in reducing endoscopic, clinical, and surgical recurrence rates in adults. We aimed to report our experience with Kono-S anastomosis in children, focusing on its feasibility and postoperative complications. METHODS: We retrospectively analyzed pediatric CD patients who underwent ICR with Kono-S anastomosis between August 2022 and May 2023. Data on demographics, clinical characteristics, surgery, hospitalization, and follow-up including colonoscopy were collected. Complications were classified using the Clavien-Dindo classification. RESULTS: Twelve patients (7 females, 58.3%) were included. Six (50%) of the patients had the B3 luminal form of the disease (according to Paris classification). Median surgery duration was 174 (interquartile range [IQR] 161-216) minutes. Anastomosis creation took a median of 62 (IQR, 54.5-71) minutes. Median hospitalization length was 6 (IQR 4-7) days. No short- or mid-term complications were observed. Median follow-up duration was 9.5 (IQR 6.8-12) months. CONCLUSION: According to our results, Kono-S anastomosis is safe and feasible in pediatric CD patients, with no observed postoperative complications. These findings support the potential benefit of using Kono-S anastomosis as a treatment approach in children with CD.
Keywords: Crohn Disease; Postoperative Complications; retrospektivní studie; Kono-S; Child; dítě; Crohnova nemoc; Adult; dospělí; pooperační komplikace; anastomóza chirurgická; Endoscopy; lidé; ženské pohlaví; Humans; Anastomosis, Surgical; Pediatric surgery; Postoperative complication; Retrospective Studies; Female; Crohn’s disease